اسبابِ بغاوتِ ہند: نسخۂ برٹش لائبریری لندن کے متن کی تدوین: Causes of the Indian Revolt: Critical Edition of the Manuscript Held in British Library London - Chohan, Hafiz Safwan Muhammad (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2022)
Abstract Sir Syed’s An Essay on the Causes of the Indian Revolt did lose its very raison d’etre just before it went into press because the British Crown had taken the government of India in her own hands from the East India Company (EIC). The pamphlet chiefly concerns itself with the rule of EIC in Hindustan, and this was rolled back before it got published. It has not, however, gone unnoticed eversince for carrying many significant features and is very often referred to in historical as well as literary discussions. Author of this article got its facsimile copy from British Library London, edited its text, prepared critical edition and published it with as many as 26 annexures that are vital for understanding this text and the worldview of the Revolt of 1857. By going deep into the lexis, the author posits that only this pamphlet is not sufficient for understanding Sir Syed’s actual stance since he wrote it in Urdu, and that too, only for the concerned officers of the then government. Sir Syed managed to get this pamphlet rendered into English after 15 years which, as the author holds, is necessary for this understanding. Since the original text of this pamphlet was never available to researchers, all previous compilations are therefore based on the copy that was produced by the scribe who worked on the 1st edition of Hayat e Javed (1901). This compilation, ie, edition 2021, thus provides the most authentic text of this revered pamphlet of the colonial India. Key words: Indian Revolt 1857, Text, Correction of text, Victoria Proclamation, Martial Race, Bengal Lancers, Christianization, Religious Card, National Humiliation, Fasting & Prayer Day